Development Design Labako Batik with Combine Fractal Geometry Dragon Curve and Tobacco Leaf Motif - Wulandari, Eka Yuni; Purnomo, Kosala Dwidja; Kamsyakawuni, Ahmad (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
Labako Batik is a typical batik Jember, derived from the term